Konsep Pendidikan Anti Kekerasan dalam Rumah Tangga Berdasarkan Perspektif Islam sebagai Upaya Meningkatkan Karakter Anak - Aliyah, Kharisma Nur Ainun; Darnoto (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2024)
This article aims to depict the concept and explanation related to anti-violence education within the family scope, which is beneficial for enhancing children's character. The researcher employs a qualitative research method with a literature review approach. The data sources for this article include textbooks or online books, previous journals related to the research theme, as well as various other mass media. In a household, a harmonious atmosphere is realized when the husband demonstrates strong and responsible leadership, the wife shows gentleness and affection, and the children live in peace, mutual respect, and love for each other. The family's role in shaping the character and morals of a child is crucial. The family serves not only as a gathering place for the father, mother, and children but also as a social system that profoundly influences the child's development. The family is more than just a place of residence; it is an environment that provides comfort for the child. Various aspects of development, such as socialization skills, self-actualization, expressing opinions, and even behaviors that may deviate, can evolve within the family.